Immune resistance enhancement in juvenile penaeus monodon by supplementation of diets with dried chaetoceros calcitrans - Gabotero, Shirleny Reyes (University of the Philippines Visayas, College of Arts and Sciences, Division of Biological Sciences, 2009)
The use of immunostimulants is an alternative approach in controlling shrimp diseases. As such, microalgae have been tapped for its immune enhancer potentiaThe immunostimulatory effect of freeze dried Chaetoceroscalcitrans on the non-specific cellular immune response in Penaeusmonodon was investigated. Freeze dried C. /calcitrans was incorporated in the shrimp diet at 15g and 30g per kilogram feeds and was compared with the effects of the unsupplemented (negative control) and the diet incorporated with B-1,3 glucanCurdlan ( a commercial immune enhancer) at 10g/kg (positive control). The prohenoloxidase activity (proPO), plasma protein and the total hemocyte and differential cell count were used as indicators to evaluate the effects of the different diets on the non-specific immune response in shrimp. Then, a post challenge infection with 107cfu/ml concentration of Vibrio harveyi was done to test for resistance of the shrimp after feeding of the enhanced diet for 45 days. Shrimp fed with diet incorporated with 30g/kg Chaetoceroscalcitans showed a significantly high plasma protein concentration (20.69 + 2.54 mg/ml) and prohrnoloxidase activity (6.52E-03 + 1.2x103) compared the shrimps fed with other diets. The toralhemocyte count (2.31x 107)was also high although the difference is not significant (p>0.05) with the controls. Shrimp fed 30 mg/kg Chaetoceroscalcitrans had the highest survival rate after a post challenge with 107 concentration of Vibrio harveyi. This study showed that the incorporation of 30 g/kg Chaetoceroscalcitrans could enhance the non-specific cellular immune response of shrimp. The results suggest that the use of C. calcitrans as an immune enhancer is worth to be pursued as viable alternative in increasing the immune response competence and resistance of shrimp to diseases..